Análise da sustentabilidade dos municípios do Estado do Amapá a partir dos indicadores do Programa Cidades Sustentáveis - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The Sustainable Cities Program aims to sensitize and mobilize cities to develop in an economically, socially and environmentally sustainable way, it has an online platform that includes 260 indicators grouped in 12 thematic axes that help managers to formulate a Municipal Goals Plan in order to achieve the Sustainable Development Goals established by the United Nations Organization. This paper aims to analyze the cities´sustainability degree in the state of Amapá by calculating a Municipal Sustainability Index (ISM), showing the potentialities and weaknesses of municipalities, in order to assist public managers indecision-making, as well as to stimulate society in the monitoring of public management. Data were collected using online data bases, then they were standardized and aggregated according to the same Human Development Index methodology. Each axis produced partial results that subsidized the elaboration performance ranking of the municipalities according to the ISM. Serra do Navio, Macapá e Santana stood out positively, on the other hand, Cutias e Mazagão stood out negatively. In order to explain the results of Serra do Navio, it was highlighted the investments in infraestructure applied by the company Ore Trade Industry S.A(ICOMI, Portuguese acronym)in the past, and the results of Macapá and Santana were explained by the historical importance of both for the development of the Estate, as well as their recognized relation of complementarity of functions, which introduced the creation of the Metropolitan Region of Macapá (RMM). About the results for Mazagão, which is also part of the RMM, the dissimilarity of the other two cities was attributed dueto its late insertion in the RMM justified by the historical geographical isolation of the city, that made it dificult to share the benefits of the RMM, resulting in a difference in the degree of sustainability. Cutias, on the other hand, presented an atypical below-expected result, which was justified especially by the absence of accountability
Keywords: Desenvolvimento sustentável; Indicador de sustentabilidade; Sustentabilidade - Amapá; Amapá (Estado); CNPQ::CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; CNPQ::CIENCIAS SOCIAIS APLICADAS::ECONOMIA; GESTÃO, TECNOLOGIA E INOVAÇÃO AMBIENTAL; CIÊNCIAS AMBIENTAIS DA AMAZÔNIA